Bruno’s Sunday Bloody Sunday as an Expressive Criticism - yono, Hari (Dinamika : Jurnal Sastra dan Budaya, 2019)
The research focuses on Sunday Bloody Sunday as an Expressive Criticism. The researchers apply a qualitative research using the lyrics of the song Sunday Bloody Sunday as source of data. The finding shows that the lyrics of the song Sunday Bloody Sunday is an expressive poem that conveys the message of the spirit of the Irish nationalism and patriotism that is roosted on the speaker’s world view and weltanschauung. The world of view of the speaker of the poem is that he sides with the people of Ireland who want to make the island become united in the name of the republic Ireland that comprises the whole island and wants to spread the idea through this song. This song is also an expression of the anger of the speaker of the poem that sees the presence of the British authority cannot be tolerated because they kill the unarmed civilians on and on and every Irish people can be target for the killings..